2018
DOI: 10.3171/2017.7.jns17260
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life following surgical treatment of lesions within the pineal region

Abstract: OBJECTIVE Pineal region tumors are a rare and heterogeneous group of lesions. The optimal therapeutic approach is currently a topic of controversy, particularly in light of the potential operative risks and complications. The potential beneficial effects of surgery have already been described, but information about neurological outcome and, in particular, health-related quality of life (HRQOL) is still lacking in the literature. The aim of this study was to assess the therapeutic effect of resection of pineal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…Table 5 lists the most relevant series (series with >10 pineal cysts) of the surgically treated pineal cyst from literature. [4,15,17,18,25,29-31,33] Similarly to the previously published series, our surgically treated pineal cysts are predominantly encountered in young females between the second and the third decades of life. [22,32,34,44] Four patients were <10 years old and were operated on due to the solid appearance of their pineal lesion which was suspected to be a solid primary tumor.…”
Section: Discussionmentioning
confidence: 65%
“…Table 5 lists the most relevant series (series with >10 pineal cysts) of the surgically treated pineal cyst from literature. [4,15,17,18,25,29-31,33] Similarly to the previously published series, our surgically treated pineal cysts are predominantly encountered in young females between the second and the third decades of life. [22,32,34,44] Four patients were <10 years old and were operated on due to the solid appearance of their pineal lesion which was suspected to be a solid primary tumor.…”
Section: Discussionmentioning
confidence: 65%
“…Ongoing progress in the field of microsurgery has subsequently lowered complication rates of these complex interventions. There are recent reports about primary microsurgical resection of pineal tumors with low experienced complications and improved function without prior biopsy [ 10 , 12 , 17 , 29 ]. In some of those series, no tumor of the germ cell type group was specifically mentioned [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are recent reports about primary microsurgical resection of pineal tumors with low experienced complications and improved function without prior biopsy [ 10 , 12 , 17 , 29 ]. In some of those series, no tumor of the germ cell type group was specifically mentioned [ 10 , 17 ]. Still, permanent “minor” morbidity—double vision, hypacusis, and cerebellar symptoms—was reported for 13% of patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCs in the general population are mostly considered normal anatomical variations and the Electronic supplementary material The online version of this article (https://doi.org/10.1007/s00381-020-04792-3) contains supplementary material, which is available to authorized users. parameters to define pathological PCs in need of treatment are currently unestablished [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…As such, surgically treated pediatric PCs may represent a different and unique entity in clinical practice, which has not previously been properly investigated. Only a few large series on surgically treated PCs have been published in recent years [10][11][12][13][14][15][16][17][18][19][20][21][22], and no clinical study on surgically treated PCs in pediatric patients has been reported thus far. In 2013, a review on surgically treated PCs in children was performed.…”
Section: Introductionmentioning
confidence: 99%